FRI0005 Production of anti-citrullinated protein antibodies by B cell subsets isolated from peripheral blood of patients with rheumatoid arthritis. (23rd January 2014) - Kerkman, P.F.; van der Voort, E.I.; Trouw, L.A.; Huizinga, T.W.; Toes, R.E.; Scherer, H.U.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are among the most important molecular candidates that could drive the inflammatory immune response in a subset of patients with rheumatoid arthritis (RA). Although many aspects of the ACPA immune response have been studied, phenotype, origin and quantity of ACPA producing B cells are still unknown. Objectives: To study the capacity of peripheral blood circulating B cells and B cell subsets of RA patients for the production of ACPA. Methods: Peripheral blood B cells from patients with ACPA positive RA, ACPA negative RA and from healthy donors were isolated based on the expression of CD19 using magnetic beads. In addition, plasmablasts as well as memory and naïve B cell subsets were isolated by FACS sorting based on the expression of surface markers CD19, CD20 and CD27. Isolated B cell populations were either cultured in vitro in the presence of anti-IgM, IL-21 and BAFF on a layer of irradiated CD40L transfected fibroblasts, or left in medium without additional stimulation. Following culture for 6 and/or 13 days, supernatants were assessed for the presence of ACPA-IgG and total IgG by ELISA. Results: Following stimulation of the entire CD19+ B cell population, ACPA could be detected in up to 100% of culture wells. Both the average ACPA titer in the wells as well as the percentage of positive wells correlated with measures of disease activity as well as ACPA serum titer. Importantly, the ACPA reactivity detected was specific for citrullinated antigens, as no reactivity was observed against the arginine containing control antigen. In addition, no ACPA production was detectable by B cells isolated from ACPA negative RA patients or healthy controls. Of interest, ACPA production was independent of BCR-triggering with anti-IgM and also observed, although in lower quantities, without any stimulation. FACS-sorting experiments comparing isolated B cell subsets (CD20-CD27++ plasmablasts and CD20+CD27-/+ naïve/memory B cells) versus the remaining fraction depleted of the respective subset indicated that spontaneous ACPA production resides, for a large part, in the circulating plasmablast population. Conclusions: Our results indicate the presence of B cells capable of ACPA production in the peripheral blood of ACPA positive RA patients. ACPA production by these B cells is observed spontaneously in vitro, and can be enhanced by broadly stimulating the B cell compartment. Based on the data presented, we hypothesize that ACPA producing B cells in peripheral blood predominantly reside in the plasmablast population, and that broadly stimulating the B cell repertoire generates a cytokine environment that enhances plasmablast survival. So far, our data do not support the existence of ACPA-positive memory B cells. These observations enhance our understanding of the origin of ACPA in serum and could be relevant for the generation of future targeted therapies. Disclosure of Interest: None Declared